(untitled) (Indian Journal of Animal Production and Management, 2018)
The experiment was carried out with10 Jersey crossbred and 10 Holstein-Friesian crossbred cows during each of the four seasons viz. Pre-monsoon, Monsoon, Post-monsoon and Winter during the year 2016- 17 to study the effect of feeding practice, genetic group and season on the cost of production of milk and milk products such as paneer and curd (dahi) of crossbred lactating cows reared under organized farm condition. The overall mean cost of production of milk, paneer and and curd (dahi) was ₹ 31.73±0.55, 266.47±2.89 and 84.17±0.75 per kg, respectively. There was highly significant difference (p<0.01) of all the factors on the cost of per kg milk and its products, except the cost of per kg paneer which did not differ significantly between the two genetic groups. The cost of per kg milk production (₹ 30.46±0.55) and curd (dahi) preparation (₹ 82.91±0.65) was significantly lower on TMR than conventional feeding practice. The Holstein-Friesian crossbred had significantly lower cost of per kg milk production (₹ 29.98±0.64) and curd (dahi) preparation (₹ 82.43±0.62) than the Jersey crossbred cows. Of all the four seasons, lowest cost was found during winter in respect of all the parameters. The cost of per kg paneer preparation was significantly lower on TMR feeding (₹ 249.48±2.80) and higher in Holstein-Friesian crossbred cows.